Respuesta :
Step 1: Rewrite equation
10-5y=3x
Step 2: To get y alone on the left side, subtract 10 on both sides
10-5y=3x
-10 -10
__________
-5y=3x-10
Step 3: divide -5 on both sides, again to get y alone
-5y=3x-10
/-5 /-5 /-5
________
y=-3/5x+2
Final equation: y=-3/5x+2
Hope this helps :)
10-5y=3x
Step 2: To get y alone on the left side, subtract 10 on both sides
10-5y=3x
-10 -10
__________
-5y=3x-10
Step 3: divide -5 on both sides, again to get y alone
-5y=3x-10
/-5 /-5 /-5
________
y=-3/5x+2
Final equation: y=-3/5x+2
Hope this helps :)
Answer:
Step-by-step explanation:
put 10-5y=3x in y=mx+b form
10-5y=3x
Collecting like terms
-5y = 3x -10
Dividing by -5
y = -3/5x + 10/5
y = -3/5x + 2
Comparing to y=mx+b
m = -3/5 and b = 2